2016
DOI: 10.2147/ndt.s100405
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of psychotropic medication use in inpatient and outpatient psychiatric settings in Saudi Arabia

Abstract: ObjectiveTo study the pattern of psychotropic medication use and compare this pattern between inpatient and outpatient psychiatric settings in Saudi Arabia.MethodThis cross-sectional observational study was conducted between July 2012 and June 2014 on patients seeking psychiatric advice at major hospitals in five main regions of Saudi Arabia. Male (n=651) and female (n=594) patients who signed the informed consent form and were currently or had been previously using psychotropic medications, irrespective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…We found only 1.2% of the elderly mentally ill patients prescribed with paroxetine, a first-line SSRI. Our finding concurs with the report of Alosaimi et al that 1.8% inpatients and 4% outpatients in Saudi Arabia were prescribed paroxetine ( Alosaimi et al, 2016 ). However, the prescription pattern in our setting contrasts with the findings of Bhattacharjee et al reporting the extensive use of paroxetine ( Bhattacharjee et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…We found only 1.2% of the elderly mentally ill patients prescribed with paroxetine, a first-line SSRI. Our finding concurs with the report of Alosaimi et al that 1.8% inpatients and 4% outpatients in Saudi Arabia were prescribed paroxetine ( Alosaimi et al, 2016 ). However, the prescription pattern in our setting contrasts with the findings of Bhattacharjee et al reporting the extensive use of paroxetine ( Bhattacharjee et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, the antianxiety medications that were mainly used to treat patients with primary bipolar disorders were the only medications that retained the positive correlation with physical activity after adjusting for demographic and clinical characteristics. 44 Additionally, the antidepressants used in the current study, particularly tricyclic antidepressants, are associated with metabolic syndrome, which is traditionally associated with a lower physical activity profile. 45 , 46 However, the current findings should be interpreted with caution for several reasons.…”
Section: Discussionmentioning
confidence: 96%
“…In SA, the prevalence of OCD was reported to be 3.4% to 23.1% [ 23 - 25 ]. Another cross-sectional study found that OCD affected 1.1% of inpatients (Total=443) and 3.3% of outpatients (Total=762) [ 26 ]. The difference in the prevalence of OCD in SA is affected by the regions in which SA studies are conducted and the differences in tools used to assess the prevalence of OCD.…”
Section: Reviewmentioning
confidence: 99%